2002
DOI: 10.1088/0264-9381/19/6/311
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of generic isolated horizons

Abstract: Geometrical structures intrinsic to non-expanding, weakly isolated and isolated horizons are analyzed and compared with structures which arise in other contexts within general relativity, e.g., at null infinity. In particular, we address in detail the issue of singling out the preferred normals to these horizons required in various applications. This work provides powerful tools to extract invariant, physical information from numerical simulations of the near horizon, strong field geometry. While it complement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
591
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(596 citation statements)
references
References 26 publications
4
591
0
1
Order By: Relevance
“…In fact, these conditions do hold on a null trapping horizon under the dominant energy condition, as shown below. This treatment also turns out to be compatible with the definition of weakly isolated horizon [29,31,32,33,34,35]. Consider a null trapping horizon, assumed henceforth in this section to be given by θ + ∼ = 0.…”
Section: Null Trapping Horizons and Zeroth Lawmentioning
confidence: 72%
See 1 more Smart Citation
“…In fact, these conditions do hold on a null trapping horizon under the dominant energy condition, as shown below. This treatment also turns out to be compatible with the definition of weakly isolated horizon [29,31,32,33,34,35]. Consider a null trapping horizon, assumed henceforth in this section to be given by θ + ∼ = 0.…”
Section: Null Trapping Horizons and Zeroth Lawmentioning
confidence: 72%
“…It is difficult to find a practical formalism describing all cases without some degeneracy arising in the null case, but the dual-null formalism appears to be adequate; one fixes the additional freedom in the null case by (74). In particular, no additional conditions need be imposed on the horizon itself, as compared with the variety of definitions of isolated horizons [27,28,29,30,31,32,33,34,35]. Numerical evidence that such horizons exist in practice has been given by Dreyer et al [34], who looked for and found approximately null trapping horizons, under the name non-expanding horizons.…”
Section: Null Trapping Horizons and Zeroth Lawmentioning
confidence: 99%
“…Angular momentum The total angular momentum includes matter contributions and has been derived by many different methods including those of Brown-York [40] and isolated and dynamical horizons [24,41]. Calculated on a spacelike two-surface S that respects the rotational symmetry:…”
Section: Electric and Magnetic Chargesmentioning
confidence: 99%
“…any isomorphism from the unit 2-sphere in the Lie algebra of SU (2) to S). Then it turns out that the intrinsic geometry of S is completely determined by the pull-back A i r i =: W to S of the (internal-radial component of the) connection A i on M [4]. Furthermore, W is in fact a spin-connection intrinsic to the 2-sphere S. Finally, the fact that S is (the intersection of M with) a type I isolated horizon is captured in a relation between the two canonically conjugate fields:…”
Section: Minimally Coupled Matter: Summarymentioning
confidence: 99%